Causative-consequent character of the pregnancy complications in women tobacco smoking abuse - Dudchenko, L. V. (Journal of Education, Health and Sport, 2016)
The article presents the examination data of pregnant women, dependent on tobacco smoking and the definition of social and medical risk factors for perinatal complications. It has been shown that pregnant women who are smokers, belong to a high social risk group, are socially unadapted, most of them are in a state of prolonged stress, which reduces the quality of life of this cohort of women. It has been established that the risk of tobacco smoking during pregnancy increases the frequency of complications of the function of the fetoplacental complex on the background of the increase in the level of anemia in pregnant women, the risk of abortion, fetal distress, preeclampsia and premature childbirth.